Preserving Local Culture through Digital Comics - Tri Mulyati; Dhalia Soetopo (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
Digital environment offers teachers and students with a plethora of information and resources for learning. Nowadays, students who are mostly digital natives are used to utilizing technology in their daily life. This condition should make teachers as technology leaders responsible to provide a good learning environment where the students are involved in their own learning and that best suits to them in in a particular context. Therefore, this study aimed at developing local culture based digital comics for narrative reading comprehension and inserting local culture of Banyuwangi in English language teaching. This study followed the research and development design adapting the pattern developed by Borg and Gall. Based on the result of need analysis administered to students in class VIII of SMPN 1 Kalipuro, Banyuwangi, the product was developed by inserting local culture content into narrative texts in the form of digital comics. The digital comics had two titles: The Dance Competition and The Legend of Banyuwangi. The product was validated by the experts and tried out to the students. The result showed that the local culture based digital comics were applicable to be used in the teaching and learning narrative text reading comprehension.